Metal-binding promiscuity in artificial metalloenzyme design. (April 2015) - Pordea, Anca
Highlights: Metalloenzyme binding sites can accommodate a diverse range of metals. Metal substitution can lead to novel catalytic activity. Computational screening and rational design can identify promiscuous binding sites. Abstract : This review presents recent examples of metal-binding promiscuity in protein scaffolds and highlights the effect of metal variation on catalytic functionality. Naturally evolved binding sites, as well as unnatural amino acids and cofactors can bind a diverse range of metals, including non-biological transition elements. Computational screening and rational design have been successfully used to create promiscuous binding-sites. Incorporation of non-native metals into proteins expands the catalytic range of transformations catalysed by enzymes and enhances their potential for application in chemicals synthesis.